An assessment of nurses' knowledge regarding noise in intensive care units in Jordan. (2020) - Al-Tarawneh, Omar M.; D'emeh, Waddah M.; Yacoub, Mohammed Ibrahim
Abstract: Background: Noise in intensive care units (ICUs) is harmful and might delay patients' recovery and lengthen their hospital stay. Also, noise exposure has been known to have many adverse effects on professionals working in these settings. There is a lack of knowledge among health care providers regarding ICUs noise issue. Purposes: To assess the knowledge of Jordanian ICUs nurses regarding noise, and to determine the association among their knowledge and certain demographic variables. Method: A descriptive correlational cross sectional design was used. A total of 203 nurses working in ICUs at hospitals from major health care sectors in Jordan were recruited. Results: Findings revealed that knowledge about noise in ICUs is insufficient. The correct answer score for the entire knowledge questionnaire was 10.08 out of 21 (SD = 2.69). Also, a significant positive relationship existed between level of knowledge among ICUs nurses and their years of experience ( p  < 0.05). Conclusion: Additional efforts are required to efficiently handle ICUs noise problem especially by knowing that majority of noise sources in ICUs were modifiable. It is essential to enhance nurses' knowledge and increase their awareness regarding ICUs noise problem.